2006
DOI: 10.1086/503772
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoconvection in a Sunspot Umbra

Abstract: Results from a realistic simulation of three-dimensional radiative magnetoconvection in a strong background magnetic field corresponding to the conditions in sunspot umbrae are shown. The convective energy transport is dominated by narrow upflow plumes with adjacent downflows, which become almost field-free near the surface layers. The strong external magnetic field forces the plumes to assume a cusplike shape in their top parts, where the upflowing plasma loses its buoyancy. The resulting bright features in i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
270
7
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(333 citation statements)
references
References 14 publications
(15 reference statements)
53
270
7
3
Order By: Relevance
“…Sobotka & Puschmann (2009) also found motions of UDs, directed either into the umbra or along a faint LB. In addition, these authors, as well as Ortiz et al (2010) from spectropolarimetric observations, confirm with high spatial resolution data, the existence of dark lanes within UDs, as predicted by Schüssler & Vögler (2006).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Sobotka & Puschmann (2009) also found motions of UDs, directed either into the umbra or along a faint LB. In addition, these authors, as well as Ortiz et al (2010) from spectropolarimetric observations, confirm with high spatial resolution data, the existence of dark lanes within UDs, as predicted by Schüssler & Vögler (2006).…”
Section: Introductionsupporting
confidence: 70%
“…The bright umbral dots (UDs) and light bridges (LBs), might then represent the occasional upward intrusion of the field-free gas between the flux tubes to the surface. Schüssler & Vögler (2006) carried out realistic three-dimensional magnetohydrodynamic simulations of a plasma that is representative of sunspot umbrae. The simulations of magneto-convection in a monolithic magnetic field reaching 1.2 Mm below the surface produced UDs that are very similar to those observed in terms of brightness, size, and lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…The field lines around light bridges form a canopy structure (Jurčák et al 2006;Lagg et al 2014) with reduced field strength in the inner part. This fact supports the scenario in which light bridges are created by the intrusion of field-free (or more specifically, weak-field) plasma into the strongly magnetized sunspot umbra (Spruit & Scharmer 2006;Schüssler & Vögler 2006) through vigorous convection (Rimmele 1997;Rouppe van der Voort et al 2010;Lagg et al 2014). …”
Section: Introductionsupporting
confidence: 78%
“…Recent SOT observations from Hinode (Kitai et al 2007) indicated that these 'pointlike' umbral features have a typical diameter of approximately 250 km (a tiny fraction of the total sunspot diameter) and a lifetime of between 4 and 20 min. Patterns of weak, small-scale, convective plumes have been observed in numerical simulations of umbral convection Schüssler & Vögler 2006). Furthermore, isolated convective plumes (or 'convectons') have been found in certain simplified magnetoconvection models (e.g.…”
Section: Sunspotsmentioning
confidence: 93%